Suporte social e associação de queixa de sono com declínio cognitivo e funcional: uma coorte de 409 pessoas com demência - Campos, Tatiani Piedade De [UNIFESP] (2018)
Background: global population aging, especially in low and middle income countries as the ones in Latin America, increases the relevance of age related chronic conditions such as dementia, an important cause of disability and dependence among older people in these societies. Evidences point sleep complaints as risk factors for cognitive and functional decline and could have been associated with a worse prognosis in people with dementia. Social support has been suggested to minimize deleterious effects on people’s health and, therefore, it may minimize the effects of sleep complaints on cognitive and functional decline among those with dementia. Objective: estimate the association of sleep complaints with cognitive and functional decline in people with dementia, testing the hypothesis that an indicator of social support (having a partner) could modify these associations. Methods: secondary analysis of a dataset obtained from a longitudinal population study conducted by the 10/66 Dementia Research Group of 409 people with dementia from five Latin American countries, who were followed up for an average of 4 years. Measures from baseline: socio-demographics, marital status, sleep complaints, cognitive total scores, disability total score and number of illness. Sleep complaints were classified into four categories: (1) no sleep complaint at both baseline and follow-up, (2) sleep complaint at baseline only, (3) sleep complaint at follow-up only (4) sleep complaint at both baseline and follow-up. Measures from follow-up: sleep complaints, cognitive total scores, disability total score and number of illness. Multiple Linear Regression was used to estimate the association of sleep complaints with cognitive and functional decline in the total sample and, separately, for those who had a partner at baseline and for those who did not. All models were adjusted for potential confounders. Results: nearly one-third (31.1%) the elderly who composed the sample were over 85 years old, most of the participants were women (71.9%) and 70.3% had no partner. There was no statistically significant association between sleep complaints at any time and cognitive decline. However, risk associations were found between sleep complaints and disability when comparing complaints at follow-up to no complaints (β = 12.32, 95% CI: 4.44 – 20.21) and also when comparing sleep complaints at both, baseline and follow-up, to no complaints at all (β = 9.48, 95% CI: 1.41 – 17.54). Regarding the number of chronic diseases, the findings were similar. Those with sleep complaints at follow-up (β = 0.53, 95% CI: 0.03 – 1.02) and those with sleep complaints in both evaluations, baseline and follow-up (β= 0.83, 95% CI: 0.33 – 1.33) presented a greater risk compared to those without complaints. We also looked at the interaction effect of having a partner on these associations. There was no statistically significant interaction. However, we found stronger risk associations among those without a partner compared to those with a partner. Conclusion: we found that there was no association of sleep complaints with cognitive decline among people with dementia; however, risk associations were found between sleep complaints and functional decline, and these associations were stronger among those without a partner, strengthening the importance of social support on minimizing deleterious effects on people with dementia health. Other studies with better measures of social support and sleep complaints, as well as a longer follow-up are necessary for a better understanding of these associations.